Anthropogenic and climatic influences on the eutrophication of large estuarine ecosystems - Hans W. Paerl; Lexia M. Valdes; Benjamin L. Peierls; Jason E. Adolf; Lawrence Jr. W. Harding (Limnology and Oceanography, 2006)
We examined the effects of anthropogenic and climatic perturbations on nutrient—phytoplankton interactions and eutrophication in the waters of the largest estuarine systems in the U.S.A., the Chesapeake Bay (CB), Maryland/ Virginia, and the Neuse River Estuary/Pamlico Sound (NRE/PS) system, North Carolina. Both systems have experienced large post‐World War II increases in nitrogen (N) and phosphorus (P) loading, and nutrient reductions have been initiated to alleviate symptoms of eutrophication. However, ecosystem‐level effects of these nutrient reductions are strongly affected by hydrologic variability, including severe droughts and a recent increase in Atlantic hurricane activity. Phytoplankton community responses to these hydrologic perturbations, including storm surges and floods, were examined and when possible, compared for these systems. In both systems, the resulting variability in water residence time strongly influenced seasonal and longer‐term patterns of phytoplankton biomass and community composition. Fast‐growing diatoms were favored during years of high discharge and short residence time in CB, whereas this effect was not observed during high discharge conditions in the longer residence time NRE/ PS. In the NRE/PS, all phytoplankton groups except summer cyanobacterial populations showed decreased abundance during elevated flow years when compared to low flow years. Although hurricanes affected the CB less frequently than the NRE/PS, they nonetheless influenced floral composition in both systems. Seasonally, hydrologic perturbations, including droughts, floods, and storm‐related deep mixing events, overwhelmed nutrient controls on floral composition. This underscores the difficulty in predicting seasonal and longer‐term phytoplankton production and compositional responses to nutrient input reductions aimed at controlling eutrophication of large estuarine ecosystems.